1995
DOI: 10.1111/j.1439-0434.1995.tb00664.x
|View full text |Cite
|
Sign up to set email alerts
|

Chrysanthemum Stem Necrosis Caused by a Possible Novel Tospovirus

Abstract: Necrotic lesions surrounded by yellow areas on leaves followed by stem necrosis were observed on chrysanthemum plants cultivated in Atibaia, Sào Paulo State, Brazil. The host range, in vitro properties and particle morphology of the causal virus were typical of a Tospovirus. Serological studies demonstrated that the virus differed from tomato spotted wilt. tomato chlorotic spot, groundnut ringspot and inpatiens necrotic spot Tospoviruses. The virus isolate is thus possibly a representativeof a new serogroup of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 14 publications
0
24
0
3
Order By: Relevance
“…It was originally described as either belonging to a new serogroup of TSWV or a possible novel tospovirus and was tentatively designated Chr 1 or Chry 1. Symptoms caused by the virus were described as necrotic lesions surrounded by yellow areas on leaves followed by necrosis on stems, peduncles and floral receptacles (Duarte et al, 1995). A lesion on the stem of chrysanthemum caused by an outbreak of CSNV in the UK is shown in Figure 1d.…”
Section: Chrysanthemum Stem Necrosis Virus (Csnv)mentioning
confidence: 98%
“…It was originally described as either belonging to a new serogroup of TSWV or a possible novel tospovirus and was tentatively designated Chr 1 or Chry 1. Symptoms caused by the virus were described as necrotic lesions surrounded by yellow areas on leaves followed by necrosis on stems, peduncles and floral receptacles (Duarte et al, 1995). A lesion on the stem of chrysanthemum caused by an outbreak of CSNV in the UK is shown in Figure 1d.…”
Section: Chrysanthemum Stem Necrosis Virus (Csnv)mentioning
confidence: 98%
“…CSNV has been reported previously on chrysanthemum (Duarte et al 1995) and tomato (Kuwabara and Sakai 2008;Nagata et al 1998), but this report is the first in the world of CSNV infecting aster and Russell prairie gentian plants. The NP gene nucleotide sequence data, which were identical among CSNV isolates from chrysanthemum, tomato, aster, and Russell prairie gentian, indicated that these CSNV isolates share a common origin.…”
mentioning
confidence: 67%
“…Owing to their broad host range, multiple vector species, and appearance of new species, tospoviruses have become distributed worldwide and cause serious economic losses in many agricultural crops and ornamental plants (German et al 1992). CSNV was first reported on chrysanthemum (Dendranthema grandiflorum) in Brazil (Duarte et al 1995), and later in the Netherlands (Verhoeven et al 1996), the United Kingdom (Mumford et al 2003), and Japan (Matsuura et al 2007). CSNV also occurs on tomato (Lycopersicon esculentum) in Brazil (Nagata et al 1998) and Japan (Kuwabara and Sakai 2008).…”
mentioning
confidence: 98%
“…However, symptoms of CSNV are more severe and can cause complete necrosis of the stem leading to wilting of sections of plants (Verhoeven et al 1996). Duarte et al (1995) reported necrotic lesions surrounded by yellow areas on leaves followed by necrosis on stems, peduncles and floral receptacles due to CSNV in Brazil. …”
Section: Symptomsmentioning
confidence: 99%
“…Chrysanthemum stem necrosis virus (CSNV) was first recognised on chrysanthemum in Sao Paulo state in Brazil (Duarte et al 1995) and described as a new virus (rather than a strain of Tomato spotted wilt virus (TSWV)) by Bezerra et al (1996). The virus is spread by the thrips vectors F. occidentalis and F. schultzei (Bezerra et al 1999;Nagata and de Ávila 2000), both of which are present in Australia.…”
Section: Introductionmentioning
confidence: 99%